Analisis Faktor yang Mempengaruhi Financial Distress - Anita Tarihoran; Yola Yolanda; Robinhot Gultom (Jurnal Ilmiah METHONOMI, 2024)
This research aims to determine and analysis of factors affecting Financial Distress at manufacturing company listed in Indonesia Stock Exchange Period 2020-2022. The population in this research were 310 companies. The sampling method used in this research was purposive sampling. The data testing method used is multiple linear regression analysis with IBM SPSS 25. The results show that Profitability (ROA), Leverage (DER) and firm Value have effect on Financial Distress (Altman Z-Score), liquidity (CR) have no effect on Financial Distress (Altman Z-Score) of manufacture companies listed in Indonesia Stock Exchange for the 2020-2022 period.